Positional Context of Myonuclear Transcription During Injury-Induced Muscle Regeneration - Buckley, Kole H.; Nestor-Kalinoski, Andrea L.; Pizza, Francis X. (Frontiers in Physiology, 2022)
Fundamental aspects underlying downstream processes of skeletal muscle regeneration, such as myonuclear positioning and transcription are poorly understood. This investigation begins to address deficiencies in knowledge by examining the kinetics of myonuclear accretion, positioning, and global transcription during injury-induced muscle regeneration in mice. We demonstrate that myonuclear accretion plateaus within 7 days of an injury and that the majority (∼70%) of myonuclei are centrally aligned in linear arrays (nuclear chains) throughout the course of regeneration. Relatively few myonuclei were found in a peripheral position (∼20%) or clustered (∼10%) together during regeneration. Importantly, transcriptional activity of individual myonuclei in nuclear chains was high, and greater than that of peripheral or clustered myonuclei. Transcription occurring primarily in nuclear chains elevated the collective transcriptional activity of regenerating myofibers during the later stage of regeneration. Importantly, the number of myonuclei in chains and their transcriptional activity were statistically correlated with an increase in myofiber size during regeneration. Our findings demonstrate the positional context of transcription during regeneration and highlight the importance of centralized nuclear chains in facilitating hypertrophy of regenerating myofibers after injury.